L’exposition, un contexte de collaboration sur la scène mondiale de l’art : un cas de figure, l’art africain contemporain - Couture, Francine (Muséologies, 2018)
This analysis of the context of the globalization of the contemporary art scene is based on the concept of the cooperative network of the art worlds, as defined by the American sociologist Howard Becker, applied to the exhibition's sociological character. It is approached as a sociocultural event furthering the establishment of a cooperative network among artists, commissioners, critics and theoreticians who acknowledge in the exhibited works a certain number of values and ideas about art which they share to various degrees. Case studies from the corpus of contemporary African-art exhibitions that have been labelled as contemporary African art on the international stage serve as illustrations for this analysis.